Master plan design in developing village tourism potential with a Community Participatory Model - Puput Risdanareni; Cynthia Permata Dewi; Nindyawati Nindyawati; Titi Rahayuningsing; Dwi Prastiyo; Adi Susetyo (University of Merdeka Malang, 2023)
Pait Village, located in Kasembon Sub-district of Malang Regency, is a village with high natural tourism potential. However, the allure of tourism in Pait Village, which is located in a green area and surrounded by rivers and waterfalls, still lacks development. Carrying the main mission to increase the tourism potential in Pait Village, the community service team will develop a water tourism design in the form of a multifunctional fishpond. This fishpond will solve the problem of water surplus due to agricultural land runoff. In addition, this pond can be an alternative source of animal protein for residents and an integrated water tourism location in the Kasembon Area. The implementation method carried out in this program is to analyze the needs of the Pait village integrated Master Plan design with a community participatory model. The results of the Pait Village water tourism master plan design are in the form of a 3D mockup of water tourism and a cultivation pond that can be used as an amphitheater along with the regional expenditure budget plan (RAB).